Halal Pharmaceutical Development in Indonesia - Nekha , Aviyu (SMART Insight, 2023)
This study attempts to map research related to Halal pharmaceutical in Indonesia published by Dimensions indexed journals from 2006 to 2023. NVivo 12 Plus was used to conduct thematic studies and frequency was used to evaluate 109 publications in the scientific literature. The results found that there was a fluctuating number of publications from year to year related to Halal pharmaceutical research in Indonesia, indicating that this topic is an interesting topic and should continue to be developed. In addition, various foci of discussion and cluster analysis that describe research paths in Halal pharmaceutical research in Indonesia include Gelatin Source and Halal Pharmaceutical, Supply Chain Traceability in Indonesia Halal Pharmaceutical Industry, Halal Certification Challenges in Food and Pharmaceutical Industry, and Innovative Halal Alternatives in Pharmaceutical Formulations. This research can be used as a starting point for experts to build graphic visualizations of Halal pharmaceutical research patterns in Indonesia in published scientific research.